A Comparison of Two Invasive Techniques Unilateral and Bilateral Celiac Plexus Block in The Management of Relieving Pain in Advanced Upper Abdominal Cancer Patients (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the effectiveness of two invasive techniques of pain relief treatment with celiac block.Methodology: This is a randomized control trial study, carried out in the Department of Anaesthesiology, Shaikh Zayed Hospital Lahore, during a period of 1 year from January 2012 to January 2013. The data was entered in SPSS version 19 and analyzed. The student t test was applied for induction of hypotension after celiac block and Chi-square test was applied for pain with coin scale. Both male and female patients of 15->65 years of age. The study comprised of 100 patients, 50 in each group. P value
Keywords: Celiac plexus block, Cancer, CT guided, Neurolysis.